Tailoring registered dietitian and occupational therapy services for home-delivered meal recipients: feasibility study protocol for a randomized controlled trial - Lisa A. Juckett; Shivam Joshi; J. Madison Hyer; Govind Hariharan; Kali S. Thomas; Tejeswini Siva Sathya; Mequeil L. Howard; Leah E. Bunck; Melinda L. Rowe; Andrea Devier; Kelly Parrett; LifeCare Alliance SixtyPLUS Team (Pilot and Feasibility Studies)
Abstract Background Home-delivered meal recipients often present with complex nutritional and functional needs that place them at elevated risk for health decline and potential institutionalization. To address these complex needs, clinical services—namely registered dietitian and occupational therapy services—may be warranted to reduce the risk of health decline and maximize outcomes of this vulnerable older adult population. Accordingly, this study will explore the feasibility of testing four different clinical service models with home-delivered meal recipients. In particular, this study will determine the feasibility of recruiting and retaining participants from one home-delivered meal provider, determine challenges and opportunities to improve data collection procedures, assess resources needed to conduct study activities, and identify if service models can be implemented as intended. Methods This is a feasibility RCT with 1:1:1:1 allocation to four service arms: (a) meals only, (b) meals + registered dietitian services, (c) meals + occupational therapy services, or (d) meals + registered dietitian services + occupational therapy services. Study activities will be conducted in collaboration with one, large community-based agency in the Midwest United States. We will recruit 60 participants who meet the following inclusion criteria: is eligible to receive home-delivered meals funded through Title 3 of the Older Americans Act, has a self-reported diagnosis of diabetes and/or heart disease, is at risk for falling, and can store and reheat up to 14 frozen meals per week. Data collection will occur at baseline and at 3 months after informed consent to assess malnutrition risk, self-management of health conditions, and fall risk. Discussion While tailored dietitian and occupational therapy services may be warranted to address the nutritional and functional needs of home-delivered meal recipients, the effect of these services on recipient outcomes has yet to be rigorously examined. This feasibility study will identify the degree to which our service models can be tested with one community-based agency and identify opportunities to improve study procedures prior to conducting a definitive, stage III randomized controlled trial. Trial registration NCT06059404.